Isolation and characterisation of ascomycetes isolated from Eurycoma longifolia Jack and Malay traditional vegetables - Mohd Zainudin, Nur Ain Izzati; M., Nur Adni; Midin, Mohd Razik (Universiti Putra Malaysia Press, 2017)
Plants are the most common host for fungal communities. However, vegetables and herbs traditionally consumed by the Malay community have not been thoroughly investigated for their association with fungi. The main objective of the present study is to identify the Ascomycetes fungi associated with Eurycoma longifolia Jack and vegetables traditionally consumed by the Malay community. In the present study, we isolated and identified 34 isolates of the Ascomycetes fungi obtained from five traditional vegetables (Oenanthe javanica, Cosmos caudatus, Persicaria odorata, Psophocarpus tetragonolobus and Cantella asiatica) and Eurycoma longifolia Jack. The isolates are identified as eight species, which are Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger, Fusarium oxysporum, Fusarium proliferatum, Fusarium solani, Penicillium paraherquei and Trichoderma asperellum. Aspergillus and Fusarium are dominant among the isolated fungi. This report provides additional information on the diversity of fungi isolated from traditional vegetables and Eurycoma longifolia based on the Internal Transcribed Spacer (ITS) sequence analysis.